Al-Rahnu-led Islamic sustainable finance - Mohd Zain, Nor Razinah; Hasan, Aznan; Yusof, Siti Ainatul Mardhiah (Routledge, Taylor & Francis Group, 2024)
The expansion of Islamic sustainable finance in the financial market depends on the application of Sharī‘ah-compliance mechanisms. Many of these mechanisms can be found from the innovative financial products which are made available by Islamic financial services providers. Ar-Rahnu or Islamic pawnbroking is one of the accepted Islamic financial products utilized to enhance initiatives in providing better solutions for social, economic, and environmental issues that are happening in many countries. The application of Ar-Rahnu and its availability to the public depend on the growth of Islamic banking and finance in the country, as well as the acceptance and practices of the community. Based on the qualitative and legal doctrinal analysis, this study focuses on the application of Ar-Rahnu as one of the suitable instruments for Islamic sustainable finance. The study finds that Ar-Rahnu, treated as one of the microfinancing products, offered through Islamic banks, independent microfinance institutions, and cooperative bodies, is used immensely in providing emergency funding for those who are in need. This is especially impactful during and in the aftermath of COVID-19 pandemic between the early months of 2020 and the middle of 2022. The involvement of gold is common in the practice of Ar-Rahnu. Meanwhile, other valuable assets can be used in Ar-Rahnu mechanism, such as buildings or lands. However, such practice is not common currently due to the lack of legal recognition.